Readiness of Grade 11 Students at SMAN 1 Ciruas in Determining a Career - Rahmawati; Ahmad Baehaqi; Yunisa Prestisia Murtidewi; Yesha Rahmadita; Mirnawati; Alifah Salsabila; Wafiq Azizah; Yolinda Evinalisa; Vanesha Amanda Fritania; Rizky Amelia; Ehan Fuazan Rahmatillah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Based on the Law on we can see that education is one of the goals Education is to equip students to have skills that will be available in the future supports the fulfillment of requirements and demands work. Adequate skills constitute a person's material requirements to be able to work. In making career decisions, high school students are at a critical stage (late adolescence) between two very decisive choices. First, to choose to continue studying high or related to the world of work. Second, to reach inner maturity career selection to face both options (Achmad Juntika Nurihsan & Akur Sudianto, 2005: 2). Middle School students Upper (high school) in determining his career choice requires some consideration beforehand make decisions. Decision-making a career characterized by determination Career choice is an important issue for students High School (SMA), because it will determine the direction of his career in the future come. Keywords:,.